Reliability of cross-cultural adapted Turkish version of the Pediatric Outcomes Data Collection Instrument (PODCI) - (:unkn) unknown (IOS PRESS, 2016)
BACKGROUND: The Pediatric Outcomes Data Collection Instrument (PODCI) has been created to evaluate functional status, to assess therapeutic needs and changes after treatment in 2 to 18 years old children and adolescents who have orthopedic problems. The PODCI has three forms; parent form for children, parent and self report forms for adolescents. Instrument has 86 items assessing 'upper extremity and physical function', 'transfer and basic mobility', 'sports and physical function', 'pain/comfort', 'happiness', 'global functioning' and 'expectations from treatment domains'. The PODCI has been validated in multiple languages. The aim of this study was to investigate the reliability of the cross-cultural adapted Turkish version of the PODCI parent forms for children and adolescents in a variety of chronic musculoskeletal disorders. METHOD: This was a methodological study. The instrument was translated and cross-culturally adapted into Turkish. Turkish version was called Bedensel Islevsellik Degerlendirme Araci (BIDA). It was completed by the parents/caregivers of ninety-eight children and adolescents being treated at Marmara University Medical School Department of Physical Medicine and Rehabilitation outpatient clinics at the baseline and 2-4 weeks after between April 2013-October 2013. Internal consistency and test-retest reliability (ICC) were determined. RESULTS: Internal consistency of the subscales and test/retest cronbach alpha values were 0.90-0.91 (r = 0.71, p = 0.000) for upper extremity and physical function; 0.95-0.95 (r = 0.84, p = 0.000) for transfer and basic mobility; 0.93-0.91 (r = 0.78, p = 0.000) for sports and physical functioning; 0.77-0.82 (r = 0.45, p = 0.000) for happiness and 0.96-0.96 (r = 0.82, p = 0.000) for global functioning. Pain/comfort subscale showed low internal consistency (-0.38-0.49; r = 0.34, p = 0.004). CONCLUSION: The Turkish version of the PODCI was found to be a reliable instrument to evaluate functionality of children and adolescents with chronic musculoskeletal disorders.
Keywords: PODCI; reliability; musculoskeletal disorders; FUNCTIONAL HEALTH QUESTIONNAIRE; QUALITY-OF-LIFE; CHILDREN; ADOLESCENTS; ADAPTATION; VALIDITY; SELF